2019
DOI: 10.1111/anec.12634
|View full text |Cite
|
Sign up to set email alerts
|

A Population‐wide study of electrocardiographic (ECG) norms and the effect of demographic and anthropometric factors on selected ECG characteristics in young, Southeast Asian males—results from the Singapore Armed Forces ECG (SAFE) study

Abstract: Background: Routine use of pre-participation electrocardiograms (ECGs) has been used by the Singapore Armed Forces, targeting early detection of significant cardiac diseases. We aim to describe the impact of demographic and anthropometric factors on ECG variables and establish a set of electrocardiographic reference ranges specific to a young male multiethnic Southeast Asian cohort. Methods and results:Between young male conscripts underwent pre-participation screening that included a 12lead ECG, demographic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 39 publications
(63 reference statements)
0
12
0
1
Order By: Relevance
“…ECG screening is, however, influenced by a variety of factors, including demographics and anthropometrics. In addition, electrocardiographic parameters vary across different ethnicities compared with international norms [9]. To date, few studies have reported validation of this new criterion in Chinese populations [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…ECG screening is, however, influenced by a variety of factors, including demographics and anthropometrics. In addition, electrocardiographic parameters vary across different ethnicities compared with international norms [9]. To date, few studies have reported validation of this new criterion in Chinese populations [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Ch. Sia et al (38) disclosed that systolic blood pressure of >140 mmHg or diastolic blood pressure of >90 mmHg independently increased the prevalence of increased QRS voltage on ECG. The current study ndings also indicated higher R wave amplitude in the patients with ischemic heart disease, while no signi cant ECG changes were found in those with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…ECG screening is commonly used to identify pathological processes, such as lethal arrhythmias associated with short-or long-term QT interval. Although such conditions rarely occur in young and healthy populations, early detection can prevent the catastrophic complications of sudden cardiac death (8). Due to the limited number of related studies conducted on the middle-aged population of Iran, this study aims to evaluate the relationship between demographic and anthropometric variables and ECG parameters in the middle-aged population of Fasa Persian cohort.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been long understood 3 that in addition to the heart size and to the ventricular myocardial mass 4 , the duration of the QRS complex is influenced by the myocyte geometry and layer orientation 5 , Purkinje fibre tree structure 6 , and depolarising ion currents 7 . It is also known that compared to males, females have shorter QRS complex 8 , 9 , and that QRS duration disparities exist between races 9 , 10 .…”
Section: Introductionmentioning
confidence: 99%